Variability of the oceanographic structures of the Southern Ocean by the FerryBox data - V. Komorin; Yu. Dikhanov; V. Bolshakov; Yu. Popov; L. Matsokin (Ukrainian Antarctic Journal, 2022)
During Antarctic summers in the 2018—2021 period, physical, chemical, and biological parameters of the upper layer of seawater were continuously recorded using the FerryBox (FB) software and measuring system installed on-board the Ukrainian krill fishing trawler F/V More Sodruzhestva. The main hydrological fronts of the South Atlantic and the Southern Ocean were crossed from Cape Town to the Antarctic Peninsula. About 800,000 one-minute FB measurements were used in this research to determine and identify marine structures. The paper aims to estimate the spatial-temporal variability of oceanographic parameters of the surface layer of water in the Southern Ocean based on the FB data analysis. We use classical methods of analysis of hydrological structures, graphical, comparative, and statistical types of analysis of the field data, as well as data from the Copernicus Marine Environment Monitoring Service (CMEMS). Trawling areas were considered as hydrological landfills. We found a decrease in the total number of front crosses: from 8.6% in the 2018—2019 season to 3.9% in the 2020—2021 season. Analysis of the quality of information obtained from the FB showed that after adjustment the measurements allow solving various oceanographic problems, such as identifying frontal zones and detailing their hydrological structure, determining surface water masses and variability of their distribution limits, highlighting significant cycles in time of the measured parameters, studying the gas component of the upper sea layer water. A comparative analysis of the results of the FB observations with the CMEMS data showed their qualitative consistency.